Chemical and biological analysis of extracts of Acorus calamus L. - Pokharel, Aaradhana; Thapa, Arjun; Karki, Homa; Yadav, Rakesh K; Bharati, Samjhana; Shrestha, Timila; Homagai, Puspa Lal; Maharjan, Binita; Shrestha, Ram Lal (Journal of Nepal Chemical Society, 2023)
The powdered plant materials of Acorus calamus were subjected to successive extraction using the cold percolation method with methanol, hexane, and chloroform solvent. Qualitative phytochemical analysis of methanol, hexane, and chloroform extracts showed the presence of alkaloids, saponins, glycosides, sterols, triterpenoids, and carbohydrates. Five different major compounds were identified by GC-MS analysis of the chloroform extract, with isoprothiolane (83.11%) being the most prevalent. The total phenolic content in the chloroform extract was calculated at 17.39 mg Gallic acid equivalent /g and the total flavonoid content was 3.37 mg quercetin equivalent/g of dry extract. The IC50 value of chloroform extract was found to be 576.19 μg/mL, and the LC50 value was found to be 66.21 μg/mL. Antibacterial activity was shown in Staphylococcus aureus in chloroform extract with a ZOI of 7 mm.